THE ROLE OF LITERATURE IN ENHANCING ENGLISH LANGUAGE SKILLS - Intan Nia Salsabila; Saralena Manik; Aditya Raffa Nanda; Naya Islah Nabila; Indi Azizah Nailah; Fitri Wiratama (PT. Intelek Cendikiawan Nusantara, 2024)
This article's goal is to learn more about how literature might improve students' English language proficiency. They employ quantitative techniques. To all English literature majors, including new and older students received a questionnaire with fifteen questions. The findings demonstrate that reading literature while learning English has a major positive effect on language proficiency. When it comes to reading, writing, and speaking English, pupils who are actively immersed in the literary study of the language exhibit more growth than those who are not. The ways that literature can improve one's English-speaking abilities will be further discussed this article's goal is to learn more about how literature might improve students' English language proficiency. They employ quantitative techniques. To all English literature majors, including new and older students received a questionnaire with fifteen questions. The findings demonstrate that reading literature while learning English has a major positive effect on language proficiency. When it comes to reading, writing, and speaking English, pupils who are actively immersed in the literary study of the language exhibit more growth than those who are not. The ways that literature can improve one's English-speaking abilities will be further discussed in this conversation, along with the ramifications for real-world English language instruction.